Impacts of inundation and drought on eukaryote biodiversity in semi‐arid floodplain soils. Issue 6 (4th February 2013) - Baldwin, Darren S.; Colloff, Matthew J.; Rees, Gavin N.; Chariton, Anthony A.; Watson, Garth O.; Court, Leon N.; Hartley, Diana M.; Morgan, Matthew j.; King, Andrew J.; Wilson, Jessica S.; Hodda, Michael; Hardy, Christopher M.
Abstract Floodplain ecosystems are characterized by alternating wet and dry phases and periodic inundation defines their ecological character. Climate change, river regulation and the construction of levees have substantially altered natural flooding and drying regimes worldwide with uncertain effects on key biotic groups. In southern Australia, we hypothesized that soil eukaryotic communities in climate change affected areas of a semi‐arid floodplain would transition towards comprising mainly dry‐soil specialist species with increasing drought severity. Here, we used 18S rRNA amplicon pyrosequencing to measure the eukaryote community composition in soils that had been depleted of water to varying degrees to confirm that reproducible transitional changes occur in eukaryotic biodiversity on this floodplain. Interflood community structures (3 years post‐flood) were dominated by persistent rather than either aquatic or dry‐specialist organisms. Only 2% of taxa were unique to dry locations by 8 years post‐flood, and 10% were restricted to wet locations (inundated a year to 2 weeks post‐flood). Almost half (48%) of the total soil biota were detected in both these environments. The discovery of a large suite of organisms able to survive nearly a decade of drought, and up to a year submerged supports the concept of inherent resilience of Australian semi‐arid floodplain soil communities under increasing pressure from climatic induced changes in water availability.